KAOLIN SEBAGAI SUMBER SiO2 UNTUK PEMBUATAN KATALIS Ni/SiO2: KARAKTERISASI DAN UJI KATALIS PADA HIDROGENASI BENZENA MENJADI SIKLOHEKSANA - Bakri, Bakri; Utari, Tresye; Sari, Indra Puspita (Makara Journal of Science, 2018)
Kaolin as a SiO2 Source for Ni/SiO2 Catalyst Syntheses: Characterization and Application of Catalyst for Hydrogenation Benzene to Cyclohexane. Kaolin one of clay minerals has been employed as a SiO2 source and produced a mixture of two type SiO2, quartz and quartz alpha, with the amount of 60 % of kaolin used. The SiO2 produced had been diverted to silica gel and used as supporting agent for Ni/SiO2 catalyst through impregnation of Ni(NO3)2 solution to form Ka and Kb catalysts, that having surface area smaller than the silica gel. The pore size and volume of Ka catalyst is bigger than Kb catalyst. Catalytic properties of Ni/SiO2 catalysts have been investigated for benzene hydrogenation and resulting Ka catalyst had produced more cyclohexane than Kb catalyst.